Indirect comparison of mobocertinib and real-world therapies for pre-treated non-small cell lung cancer with EGFR exon 20 insertion mutations - Christopoulos, Petros; Prawitz, Thibaud; Hong, Jin-Liern; Lin, Huamao M.; Hernandez, Luis; Jin, Shu; Tan, Min; Proskorovsky, Irina; Lin, Jianchang; Zhang, Pingkuan; Patel, Jyoti D.; Ou, Sai-Hong I.; et al. (Lung cancer, 2023)
Objectives - Mobocertinib, a novel oral epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor, is available for the treatment of non-small cell lung cancer (NSCLC) with EGFR exon 20 insertion (ex20ins) mutations after platinum chemotherapy. We performed an indirect comparison of clinical trial data and real-world data (RWD) to determine the relative efficacy of mobocertinib vs. other treatments for these patients. - Materials and methods - Data on the efficacy of mobocertinib from a phase I/II trial (NCT02716116) were compared to RWD from a retrospective study in 12 German centers using inverse probability of treatment weighting to adjust for age, sex, Eastern Cooperative Oncology Group score, smoking status, presence of brain metastasis, time from advanced diagnosis, and histology. Tumor response assessment was based on RECIST v1.1. - Results - The analysis included 114 patients in the mobocertinib group and 43 in the RWD group. The confirmed overall response rate (cORR) according to investigator assessment was 0% for standard treatments and 35.1% (95% confidence interval [CI], 26.4-44.6) for mobocertinib (p < 0.0001). Compared to standard regimens in the weighted population, mobocertinib prolonged overall survival (OS, median [95% CI] = 9.8 [4.3-13.7] vs. 20.2 [14.9-25.3] months; hazard ratio [HR] = 0.42 [0.25-0.69], p = 0.0035), progression-free survival (PFS, median [95% CI] = 2.6 [1.5-5.7] vs. 7.3 [5.6-8.8] months; HR = 0.28 [0.18-0.44], p < 0.0001), and time to treatment discontinuation (median [95% CI] = 2.1 [1.2-3.1] vs. 7.4 [6.4-8.5] months; HR = 0.34 [0.18-0.65], p = 0.0004). - Conclusion - Mobocertinib was associated with an improved cORR and prolonged PFS and OS compared to standard treatments for patients with EGFR ex20ins-positive NSCLC previously treated with platinum-based chemotherapy.